2010
DOI: 10.1007/s10147-010-0139-5
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal melanoma with a KIT-activating mutation, which is a target for tyrosine kinase inhibitor

Abstract: Recent advances in our understanding of the genetic mutations associated with melanoma have led to the classification of distinct melanoma subtypes. A number of reports have consistently demonstrated that mucosal and acral melanomas more commonly harbor KIT-activating mutations than do other subtypes. Success in treating gastrointestinal stromal tumors with imatinib has led to speculation that KIT-mutated melanoma might also be effectively managed using this approach. A 78-year-old woman presented with a 4-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…1. Three out of these mutations (L576P, K642E, D816N) are recurrent in MM, with the L576P substitution accounting for approximately a third of all KIT sequence alterations [5,6]. Three out of these mutations (L576P, K642E, D816N) are recurrent in MM, with the L576P substitution accounting for approximately a third of all KIT sequence alterations [5,6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1. Three out of these mutations (L576P, K642E, D816N) are recurrent in MM, with the L576P substitution accounting for approximately a third of all KIT sequence alterations [5,6]. Three out of these mutations (L576P, K642E, D816N) are recurrent in MM, with the L576P substitution accounting for approximately a third of all KIT sequence alterations [5,6].…”
Section: Resultsmentioning
confidence: 99%
“…MMs have worse outcomes as compared with the skin melanomas, that is at least in part attributed to their hidden location and, consequently, late diagnosis. imatinib, sunitinib, sorafenib, dasatinib) to this category of patients resulted in unprecedented tumor responses [5,6]. Systematic studies on somatic mutations in MM have revealed that these tumors differ from other melanoma subtypes by a unique spectrum of molecular alterations [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean survival of patients with GNAQ/11 was significantly shorter than that of wild-type GNAQ/11. 5 Furthermore, Itoh et al 6 suggest C-KIT (CD117) is overexpressed in over 80% of cases. B-type Raf (BRAF) mutations are uncommon (less than 10% of cases) in mucosal melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…These cases have marked a tendency to respond to imatinib mesylate which inhibits tyrosine kinase. Although case reports are accumulating [82,83], more data, including long-term control and prognostic data, will be necessary to confirm the effect of this agent.…”
Section: Molecular Targeted Therapymentioning
confidence: 99%